Position Paper Task force on Foreign Policy Democratic Advisory Committee - Charles Warren::::::
This document is a position paper by the Democratic Advisory Committee's Task Force on Foreign Policy, intended to stimulate debate within the California Democratic Party and inform the 1968 platform. It affirms support for international cooperation, the United Nations, arms control, economic development, and the pursuit of peace under international law, while presenting two differing perspectives on how to address the Vietnam War—one favoring an immediate halt to bombing and negotiated settlement, and another urging cautious de-escalation without risking communist victory. The paper also outlines policy recommendations regarding China, the Middle East, and global hunger, emphasizing multilateral action and mutual development rather than military confrontation. It calls for major reforms to strengthen the United Nations, promote nuclear nonproliferation, limit arms sales, and expand international legal mechanisms. Finally, it advocates robust efforts in human rights, cultural exchange, population research, economic development, and trade liberalization to advance global stability and prosperity.